2011
DOI: 10.1039/c0cc04660d
|View full text |Cite
|
Sign up to set email alerts
|

C–H activation of 2,4,6-triphenylphosphinine: unprecedented formation of cyclometalated [(P⁁C)Ir(iii)] and [(P⁁C)Rh(iii)] complexes

Abstract: An unprecedented C-H activation of 2,4,6-triphenylphosphinine by Ir(III) and Rh(III) has been observed. Time-dependent (31)P{(1)H} NMR spectroscopy gave insight into the cyclometalation reaction and the corresponding coordination compounds were characterized by means of X-ray crystallography. In contrast, 2,4,6-triphenylpyridine does not show any ortho-metalation, demonstrating a remarkable difference in reactivity between these two structurally related aromatic heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Treatment of 7 with [Cp*IrCl 2 ] 2 and NaOAc in a ratio of 2:1:2 leads initially to the quantitative formation of a new species at room temperature. This compound shows a broad signal at δ =132.4 ppm and can be assigned to the monomeric P‐coordinated neutral adduct [Cp*IrCl 2 ( 7 )] (Ir(PCH), Scheme and Figure 5) as verified before for the reaction of 1 with [Cp*IrCl 2 ] 2 and NaOAc 20…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Treatment of 7 with [Cp*IrCl 2 ] 2 and NaOAc in a ratio of 2:1:2 leads initially to the quantitative formation of a new species at room temperature. This compound shows a broad signal at δ =132.4 ppm and can be assigned to the monomeric P‐coordinated neutral adduct [Cp*IrCl 2 ( 7 )] (Ir(PCH), Scheme and Figure 5) as verified before for the reaction of 1 with [Cp*IrCl 2 ] 2 and NaOAc 20…”
Section: Resultssupporting
confidence: 70%
“…Despite the fact that the large opening of this ∢C(1)‐P(1)‐C(5) angle reflects a significant disruption of the aromaticity and consequently a high reactivity of the PC double bond is expected, all compounds can easily be isolated, handled, and characterized. We assume that the non‐metalated aryl‐substituent in the 6‐position of the heterocyclic framework might contribute to a steric protection of the PC double bond as we have observed before for the phosphinine‐Rh III and Ir III complexes of the type [Cp*M(P^C)Cl], containing a cyclometalated 2,4,6‐triphenylphosphinine ligand ( 1 ) 20…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…From the chemical shift differenceo fDd = 23.8 ppm it is, however, not conclusive whether the triazaphosphole moiety coordinates through the phosphorus or nitrogen lone pairs to the metal centre because s-coordinated phosphinines show asimilar chemical shift difference upon coordination to am etal centre ( Figure 10). [21] Crystals of 7a,s uitable for X-ray crystal-structure analysis, were obtained from cooling ah ot saturated solution of the compound in dichloromethane slowly to T = À21 8C. Compound 7a crystallises in the space group P1 and the molecular structure of the crystal, along with selected bond lengths and angles, is depicted in Figure 11;t his shows the expected facial geometry of the [L 2 Re(CO) 3 Br] complex.…”
Section: P{mentioning
confidence: 99%
“…For example, we have shown that 1 can undergo base-assisted C-H activation in the presence of [Cp*IrCl 2 ] 2 to form the neutral Ir III complex [(1)Cp*IrCl] (Figure 2). [13] In line with the isoelectronic principle, it was further demonstrated that 2-(2Ј-pyridyl)-4,6-diphenylphosphinine (2) forms the cationic Ir In several cases, however, the transition metal complexes of phosphinines are reactive towards nucleophiles. This is especially true for coordination compounds with metal centers in higher oxidation states and less-substituted phosphinines.…”
mentioning
confidence: 92%